2015
DOI: 10.1002/cctc.201402897
|View full text |Cite
|
Sign up to set email alerts
|

Binder Effects in SiO2‐ and Al2O3‐Bound Zeolite ZSM‐5‐Based Extrudates as Studied by Microspectroscopy

Abstract: Microspectroscopic methods were explored to investigate binder effects occurring in ZSM‐5‐containing SiO2‐ and Al2O3‐bound millimetre‐sized extrudates. Using thiophene as a selective probe for Brønsted acidity, coupled with time‐resolved in situ UV/Vis and confocal fluorescence microspectroscopy, variations in reactivity and selectivity between the two distinct binder types were established. It was found that aluminium migration occurs in ZSM‐5‐containing Al2O3‐bound extrudates, forming additional Brønsted aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 51 publications
3
88
0
Order By: Relevance
“…It could also be attributed to changes in the mesoporous structure during alkali treatment. Whiting et al [21] suggested that although SiO2 lacks acid sites able to take part in acid-catalyzed processes, its intimate contact with impregnated zeolite can induce solid-state ion exchange, with loss of Brønsted acidity as a result of zeolite framework dealumination.…”
Section: Silica and Alumina Bindersmentioning
confidence: 99%
“…It could also be attributed to changes in the mesoporous structure during alkali treatment. Whiting et al [21] suggested that although SiO2 lacks acid sites able to take part in acid-catalyzed processes, its intimate contact with impregnated zeolite can induce solid-state ion exchange, with loss of Brønsted acidity as a result of zeolite framework dealumination.…”
Section: Silica and Alumina Bindersmentioning
confidence: 99%
“…Calculated from the saturation adsorption amounts, the adsorption ratio for Z5-bo increased from 1.8 to 1.9 after regeneration, whereas the adsorption ratio for Z5-atp decreased from 1.9 to 1.7 after regeneration. It means that the initial para-selectivity increment for regenerated Z5-bo was not only due to the reduced acidity but partially due to the more restricted pore opening which might be caused by the aluminium species migration in alumina-bound ZSM-5 extrudates [21,31]. In the Z5-atp case, the extent of pore opening reduction decreased after regeneration, which indicated that the continuously decreased acidity of Z5-atp was the main reason for para-selectivity increment.…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Postedmentioning
confidence: 93%
“…As shown in Figure 6, the HZSM-5 catalyst exhibits three acid sites, i.e., weak (a low temperature peak at around 220 o C), medium (a medium temperature peak at around 300 o C) and strong (a high temperature peak at around 450 o C) acid sites. The amount of total acid sites of the zeolite extrudates Z5-atp and Z5-bo are much less than HZSM-5, showing the diluting effect of binders [31]. Compared with Z5-Bo, Z5-atp exhibited a lower total acidity and weaker acid strength.…”
Section: Preparation and Characteristics Of Zsm-5 Extrudatesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, when zeolites are employed in an industrial reactor, they are usually combined with a binder material and shaped into catalyst bodies, such as extrudates. [27][28][29][30] It is however not known where such additional acid sites are located and how the additional acid sites affect the performance. [24] The addition of a binder material can have a large effect on the catalytic activity, as it can, for example, influence the overall acidity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%